PERTUMBUHAN TANAMAN TOMAT (LYCOPERSICUM ESCULENTUM, MILL.) DAN TANAMAN SELA PADA POLA TANAM MONOKULTUR DAN TUMPANGSARI DENGAN TANAMAN SELA AROMATIK - Olivina S. Messakh (Partner, 2013)
Growth of Tomato (Lycopersicum esculentum, Mill.) and Intercrops of Monoculture and Aromatic-Intercropping Systems. This study is aimed to find method to increase the productivity of tomato plants per unit area of land and to find a combination of aromatic plant species and the best population of tomato plant that can enchance the productivity of tomato plants. This study uses 2 factorial randomized block design.The first factor is the aromatic plant species which consist of 4 level, namely T0: tomato monoculture, T1: intercropping tomato and lemon grass, T2: intercropping tomato and basil, T3: intercropping tomato and coriander.The second factor is tomato plant populations that consists of 3 level namely P1: population 45.000 plants/ha, P2: population 37.500 plants/ha and P3: population 32.140 plants/ha. Each combination treatment is replicated three times.The results indicate that aromatic plants species significantly affect the height of plant, leaf area, leaf area index, stem diameter, plant dry weight and the level of pest attack. Similarly, the population of tomato significantly affect the leaf area, leaf area index, fresh weight of aromatic plants and the level of pest attack. Furthermore, the interaction of aromatic plant species and population size of tomato plants significantlyaffect the leaf area and leaf area index (at 56 days after planting), fresh weight and dry weight of aromatic plants and the level of pest attack. Coriander decreases the level of pest attack which is highest at 48,50% compared to monoculture tomato. directoryKeywords: Tomato, Lemon grass, Basil, Coriander, Intercropping, Pulation